Mycoplasma hominis infections in solid organ transplant recipients: Clinical characteristics, treatment outcomes, and comparison of phenotypic and genotypic susceptibility profiles. Issue 3 (16th March 2022) - Chang, Sandy Y.; Price, Travis K.; Beaird, Omer E.; Gaynor, Pryce T.; Schaenman, Joanna M.; Carlson, Margrit E.; Kubak, Bernard M.; Yang, Shangxin; Multani, Ashrit
Abstract: Background: Mycoplasma hominis can cause significant infections after solid organ transplantation (SOT). Treatment should be guided by susceptibility testing, but conventional lab methods are laborious with prolonged turnaround time (TAT). This case series compares the phenotypic and genotypic susceptibility profiles of M. hominis isolates identified from SOT patients. Methods: This is a single‐center retrospective study evaluating SOT recipients with confirmed M. hominis infections. Patients' demographic, clinical, microbiological, and radiographic data were collected. Culture of M. hominis isolates was performed according to current Clinical and Laboratory Standards Institute guidelines. Phenotypic susceptibility testing was performed by University of Alabama Diagnostic Mycoplasma Laboratory. Whole genome sequencing (WGS) was performed followed by bioinformatic analysis of known genetic determinants of resistance. Results: Seven SOT recipients with M. hominis infections were identified. Two out of seven (28.5%) patients had resistance detected by phenotypic susceptibility testing (Case 5 to levofloxacin and Case 7 to tetracycline). Genomic analyses confirmed the presence of mutations in the parC and parE topoisomerase genes at positions conferring to fluoroquinolone resistance in the isolate from Case 5, while the tetracycline‐resistant isolate from Case 7 harbored the tetM gene. The median TAT from the date of specimen collection was 24 days for phenotypic susceptibility testing and 14 days for genotypic susceptibility testing. All seven patients received antimicrobials directed toward M. hominis and recovered with complete resolution of infection. Conclusions: WGS may offer a novel and more rapid methodology for M. hominis susceptibility testing to help optimize antimicrobial usage, but more data are needed.